Research Activity in the Czech and Slovak Regions - Vladimír Žítek; Viktorie Klímová (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
Research and development represent an important source for the introduction of new innovation, in particular technical innovation. Individual regions differ considerably in the level of their research activity and in their preconditions for it. The aim of this paper is to compare the level of research activity in Czech and Slovak regions. The analysis is carried out at the NUTS3 regions level; therefore, it involves 14 regions in the Czech Republic and 8 regions in Slovakia. Our analysis is focused on expenditures on R&D and human resources in R&D. We analyze the source of financing (public, business), field of science (technical and natural sciences), type of research (basic, applied), and the number of R&D personnel in full time equivalent. The attention is also paid to the institutions responsible for support of R&D in both countries. The level of research activity in the Czech Republic is significantly higher than in Slovakia. In both countries the research is concentrated in the capital cities and the South Moravian Region in the case of the Czech Republic. Big differences between capital cities and other regions were observed
Keywords: R12; O31; 330; research; development; innovation; region; Czech Republic; Slovakia